Comparative Studies: Education Systems in Germany and Turkey - AN, Rosyidah; Sassi, Komarudin; Al Ayyubi, Ibnu Imam (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This article discusses the differences in the education systems in Germany and Turkey. In addition, this article will discuss educational management, curriculum, materials, and assessment systems in educational institutions. The purpose of this study is to find out what are the differences in the education system in Germany and Turkey. In addition, this article will discuss educational management, curriculum, materials, and assessment systems in Educational institutions. In this study, a qualitative descriptive analytical method is used. The two sources of research materials are primary and secondary data. Primary data is textbooks, and secondary data consists of government regulations, scientific publications, journals, and other relevant articles. with current studies. Data analysis techniques include data reduction, data transmission, and conclusion drawing. The result of this study is that education in Turkey and Germany has many significant differences. The following are some of the key differences: The structure of education in Turkey is as follows, primary education lasts 8 years, secondary education lasts 4 years. Higher education in Germany includes bachelor's, master's, and doctoral programs. Here are the differences in the education system between schools in Germany and Turkey.